Saccharomyces boulardii and Bifidobacterium co-treatment for antibiotic associated diarrhea in pediatrics: a multicenter efficacy and safety study - Liu, Qianfang; Liu, Lin; Zhou, Jingwen; Duan, Yusong; Shi, Chunlin; Zeng, Yan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundRecent or ongoing use of antibiotics causes diarrhea. Probiotic yogurt is generally used in antibiotic-induced diarrhea as adjuvant therapy. In recent times, there have been no clear recommendations or guidelines for the course of treatment of probiotics in preventing antibiotic-induced diarrhea in infants and young children in mainland China. The objectives of the study were to evaluate the efficacy and safety of Saccharomyces boulardii and Bifidobacterium in antibiotic-induced diarrhea in infants and young children in Chinese settings.MethodsData were collected retrospectively. Infants and children received antibiotic treatments with 50 g daily regular yogurt and 50 g daily regular yogurt for 7 days after those treatments (AY cohort, n = 119), or with 10 billion CFU daily Saccharomyces boulardii and 10 billion CFU daily Saccharomyces boulardii for 7 days after those treatments (AS cohort, n = 110), or with 10 billion CFU daily Bifidobacterium and 10 billion CFU daily Bifidobacterium for 7 days after those treatments (AB cohort, n = 106). Two times per day loose or watery stools were considered mild diarrhea, and three or more times per day loose or watery stools were considered severe diarrhea.ResultsAll infants and young children reported diarrhea after the start of any type of antibiotic treatment with probiotics. Time for the start of diarrhea after the start of antibiotic treatments with probiotics was higher in infants and children of the AS cohort than in infants and children of the AY [3 (4–3) days versus 1 (1–1) days, p < 0.001] and the AB [3 (4–3) days versus 2 (2–1) days, p < 0.001] cohorts. Twenty-four (20%), 11 (10%), and 17 (16%) infants and children reported any type of diarrhea in the AY, AS, and AB cohorts, respectively. The number of patients with reported diarrhea (mild and severe) and the number of patients who required extra anti-diarrheal treatments after antibiotic treatments in the AS cohort were fewer than those reported in the AY and the AB cohorts (p < 0.05 for all). Yogurt reported sneezing, runny nose, redness of the eyes, and nausea in the AY cohort (p < 0.05 for all comparisons). Saccharomyces boulardii and Bifidobacterium caused vomiting and nausea.ConclusionsAny type of antibiotic treatment cause diarrhea in infants and young children. Probiotics especially Saccharomyces boulardii co-treatments with any type of antibiotic treatment, significantly reduce incidences of diarrhea in infants and young children with manageable adverse effects.